Safety and immunogenicity of a quadrivalent seasonal influenza vaccine adjuvanted with hydroxypropyl-β-cyclodextrin: A phase 1 clinical trial. Issue 31 (29th July 2022) - Watanabe, Akane; Nishida, Sumiyuki; Burcu, Temizöz; Shibahara, Takayuki; Kusakabe, Takato; Kuroda, Etsushi; Ishii, Ken J.; Kumanogoh, Atsushi
Highlights: Hydroxypropyl-β-cyclodextrin (HP-β-CyD) exhibits adjuvant function. A trial was run using an influenza vaccine adjuvanted with HP-β-CyD (Flu/CyD-vac) Flu/CyD-vac is safe and sufficiently immunogenic despite a reduced antigen dose. Hydroxypropyl-β-cyclodextrin is a promising vaccine adjuvant candidate. Abstract: Objectives: Hydroxypropyl-β-cyclodextrin (HP-β-CyD), an oligosaccharide used as an excipient in pharmaceutical preparation, was recently reported to function as a vaccine adjuvant to co-administered antigens. In this study, we investigated the safety and immunogenicity of a seasonal influenza vaccine adjuvanted with HP-β-CyD (FluCyD-vac) in healthy adults compared with those of a standard seasonal influenza vaccine (Flu-vac). Methods: We conducted a single-blinded randomized phase 1 clinical trial study, and used two quadrivalent split seasonal influenza vaccines: FluCyD-vac containing 9 μg of HA/strain and 20% w/v of HP-β-CyD, and Flu-vac containing 15 μg of hemagglutinin (HA)/strain only. All participants were randomly assigned to receive a single dose of Flu/CyD-vac or Flu-vac at a ratio of 2:1. We assessed solicited and unsolicited adverse events (AEs) and immune responses using hemagglutination inhibition (HI) titers. In addition, we assessed T-cell function in peripheral blood mononuclear cells (PBMCs), after stimulation with HA vaccine strains, using flow cytometry. Results: Among 36 healthy volunteers enrolled in the study (FluCyD-vac, n = 24; Flu-vac, n = 12), FluCyD-vac was well tolerated. Most of the solicited AEs were mild local skin reactions at the injection site. No serious AEs were reported in either group. HI titers 21 days after vaccination with FluCyD-vac were comparable with those of Flu-vac and sufficient to meet international criteria, despite reduced HA antigen doses. When PBMCs were stimulated with the four HA antigens in the vaccine, tumor necrosis factor (TNF)-α-producing CD4 + T cells were enhanced in the FluCyD-vac group. Conclusion: FluCyD-vac was well-tolerated and immunogenic, despite containing 40% less HA antigens than Flu-vac. This study showed that HP-β-CyD is a potentially safe, novel adjuvant for human influenza vaccine. Clinical trial registry: UMIN000028530.